'Choice' in occupational therapy theory: A critique from the situation of patriarchy in India. (2nd January 2021) - Murthi, Kavitha; Hammell, Karen Whalley
Abstract: Background: Dominant occupational therapy theories assert that people choose their daily occupations, and participate in occupations as autonomous agents; yet scholars insist that choices are socially-structured and inequitably available. Aim: To critically review the concept of choice in occupational therapy theory through an exploration of patriarchy in India. Material and methods: Drawing from scholarly work that addresses patriarchy in India, we employ the commonly-used occupational categories of self-care, productivity and leisure as a framework to explore the real availability of occupational choices for women. Results: Patriarchal ideology perpetuates inequitable power dynamics within Indian society. As a consequence, women, children and non-dominant men have few opportunities to make or enact occupational choices that impact their wellbeing and their lives. Conclusions: The examples provided in this paper challenge those occupational therapy theories that portray occupational engagement as the product of individual volition and unconstrained choice. Significance: Dominant occupational therapy theories are informed by specific Western assumptions that may have little relevance to people in other contexts. Critical approaches to professional assumptions are essential to avoid the imperialistic imposition of irrelevant theories, and the development and delivery of services that may be oppressive for clients who have few opportunities to make occupational choices.